Cultural Constructions of Madness in Eighteenth-Century Writing - Ingram, A. author. aut Link
X, 245 p.
Keywords: Cultural Constructions of Madness in the Eighteenth Century deals with the (mis)representation of insanity through a substantial range of literary forms and figures from across the eighteenth century and beyond. Chapters cover the representation, distortion, sentimentalization and elevation of insanity, and such associated issues as gender, personal identity, and performance, in some of the best, as well as some of the least, known writers of the period. A selection of visual material, including works by Hogarth, Rowlandson, and Gillray, is also discussed. While primarily adopting a literary focus, the work is informed throughout by an alertness to significant issues of medical and psychiatric history.